Criptógamos do Parque Estadual das Fontes do Ipiranga, São Paulo, SP. Algae, 44: Bacillariophyceae (Surirellales: Epithemia) - Morais, Krysna Stephanny De (2019)
ABSTRACT A survey of Epithemia (Bacillariophyceae) was carried out in the Parque Estadual das Fontes do Ipiranga (PEFI), São Paulo, SP, Brazil, in order to know the taxonomic diversity and the morphological variability of the genus. A total of 31 diatoms slides were analyzed of which five were used in this study. Five species were identified: E. proboscidea Kützing, E. gibba (Ehrenberg) Kützing, E. gibberula (Ehrenberg) Kützing, E. operculata (C. Agardh) Ruck & Nakov and Epithemia sp., with the dominance of periphytic species. One taxon was recorded for the first time in Brazil (E. proboscidea Kützing) and two taxa in the PEFI area (E. gibba (Ehrenberg) Kützing and E. operculata (C. Agardh) Ruck & Nakov).